PENGOLAHAN LIMBAH CAIR MINYAK KANOLA MENGGUNAKAN KOMBINASI ADSORPSI DAN MEMBRAN ULTRAFILTRASI POLIMER - Martini, Sri (KINETIKA, 2019)
Industrial oily wastewater needs treatment before its discharge to open waters or reuse purpose. Membrane filtration as one of the most reliable options for water and wastewater treatment processes can experience fouling problem, reducing its efficiency. This research studies the improvement of polymeric ultra-filtration (UF) membrane performance by integrating membrane filtration with adsorption process using activated carbon to treat raw canola oil wastewater prior to sending it through the membrane system. The results show that pre –treatment process increased the permeate flux by more than 39 % compared to using a stand-alone UF membrane. Additionally, the integrated system resulted in excellent removal efficiencies of oil, total suspended solid (TSS), total dissolved solid (TDS) and chemical oxygen demand (COD) by 97, 100, 98 and 90 %, respectively. The integrated activated carbon – UF membrane system was further investigated under different conditions of pressure (P) (1, 2, 3 bar) and velocity (V) (300, 400, 600 mL/min). Using Hermia’s model, it was assumed that the cake formation model controlled fouling regardless of the applied P and V conditions. The inclusion of the pre-treatment stage is therefore, beneficially important for improving polymeric UF membrane performance for treating industrial oily wastewater as it can increase flux permeate and lengthen membrane lifespan